Factors Associated with Functional Recovery among Patients with Low Back Pain - Khuc Thi Hong Anh (2019)
Purpose: To examine the relationships between pain, pain self-efficacy, anxiety, depression, and co-morbid diseases with functional recovery among patients with low back pain (LBP). Design: Descriptive correlational design. Methods: The sample was 126 patients with LBP who were treated in Rheumatology Unit at Bach Mai Hospital, Hanoi, Vietnam. Data were collected using patients’ hospital record and 4 questionnaires: 1) the Numerical Rating Scale, 2) the Pain Self-efficacy Questionnaire, 3) the Hamilton Anxiety Rating Scale and Hamilton Depression Rating Scale, 4) the Oswestry Disability Index. Spearman’s Rho was employed to test the relationships among studied variables. Main findings: The findings revealed that pain was negatively correlated with functional recovery (rs = - .56, p < .05), anxiety and depression were also negatively correlated with functional recovery (rs = - .46, - .58, p < .05). Pain self-efficacy was positively correlated with functional recovery (rs = .48, p < .05). Nevertheless, co-morbidity did not correlate with functional recovery (p > .05). Conclusion and recommendation: To improve patients’ functional recovery, nurses should assess and control pain, anxiety and depression as well as increase pain self-efficacy. A comprehensive guideline to improve patients’ recovery should be developed and tested for its effectiveness with research before implementation.